2016
DOI: 10.1371/journal.pone.0154250
|View full text |Cite
|
Sign up to set email alerts
|

Modified Team-Based Learning in an Ophthalmology Clerkship in China

Abstract: ObjectiveTeam-based learning (TBL) is an increasingly popular teaching method in medical education. However, TBL hasn’t been well-studied in the ophthalmology clerkship context. This study was to examine the impact of modified TBL in such context and to assess the student evaluations of TBL.MethodsNinety-nine students of an 8-year clinical medicine program from Zhongshan Ophthalmic Centre, Sun Yat-sen University, were randomly divided into four sequential units and assigned to six teams with the same faculty. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 25 publications
0
28
0
Order By: Relevance
“…For example, both teachers and students express positive feelings about the effectiveness of team-based learning in ophthalmology [14]. More recently, we demonstrated that team-based learning (TBL) can significantly improve students’ performance and engagement in an ophthalmology clerkship [15]. Additionally, problem-based learning (PBL), which requires students to work on ‘real-life’ scenarios, can stimulate student’s interest in ophthalmology and improve their clinical skills, including collecting medical history and performing eye examinations [16].…”
Section: Introductionmentioning
confidence: 99%
“…For example, both teachers and students express positive feelings about the effectiveness of team-based learning in ophthalmology [14]. More recently, we demonstrated that team-based learning (TBL) can significantly improve students’ performance and engagement in an ophthalmology clerkship [15]. Additionally, problem-based learning (PBL), which requires students to work on ‘real-life’ scenarios, can stimulate student’s interest in ophthalmology and improve their clinical skills, including collecting medical history and performing eye examinations [16].…”
Section: Introductionmentioning
confidence: 99%
“…A number of potential practices that might enhance ophthalmology teaching have been studied, such as integrated problem based learning[13]and team-based learning[14]. We have previously reported that the application of team-based learning to the ophthalmology clerkship curriculum significantly improved students’ performance[15], highlighting the importance of student engagement and interaction in learning. However, the effectiveness of the flipped classroom versus traditional lecture-based classroom in ophthalmology teaching has not been investigated worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…The TBL module was designed according to the guidance (Parmelee & Michaelsen, 2010) and included: an Individual Readiness Assurance Test (IRAT), preparatory assignments, a Group Readiness Assurance Test (GRAT), a Group Application Problem (GAP) and final examination scores (FESs). The protocol of "team-based learning" section has been published in PLoS One (Huang et al, 2016), written by the same authors of the present article. Each group was given a random topic in the first day morning of the trainee course.…”
Section: Team-based Learning Modulementioning
confidence: 99%